GEOPHYSICAL RESEARCHES OF THE LANDSLIDE TERRITORIES OF THE RIGHT BANK OF THE DNIEPER RIVER (FOREST-STEPPE ZONE) - Vyzhva, S.; Onyshchuk, V.; Onyshchuk, I.; Reva, M.; Shabatura, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper discusses the details of the application of geophysical research methods in the study of the landslide areas of the right bank of the Dnieper River within the forest-steppe zone of Ukraine. Geological and geophysical models of landslides are given. The specific tasks that are posed in studies of landslides were highlighted. There are three stages in studies of landslides which were defined: reconnaissance-methodological, detailed and monitoring. Also, sets of geophysical methods for these stages were designated. It is emphasized that the rational set of geophysical methods in the study of landslide processes is determined for each individual natural environment, taking into account: the possibility of performing field studies by a specific geophysical method on the area; the presence of differentiation of rocks by physical properties, that are used by the specific geophysical method; economic efficiency of application of the geophysical method. As an example, we described some of the results of geophysical studies, which were carried outon exemplary landslidesites onthe right bank of the Dnieper River within the forest-steppe zone of Ukraine near the Trypillia thermal power plant.
Keywords: engineering and geophysical studies; landslides; electrical resistivity; microelectric sounding; geological-geophysical models